Innovation in Waqf Management in the Digital Era to Promote Community Economy: An Implementation Analysis in West Java - Sundari, Asri; Solihin, Dadin; Anton Athoilah, Mohamad; Hasan Ridwan, Ahmad; Zaky, Muhammad (IJBLE Scientific Publications Community Inc., 2025)
The rapid development of digital technology has transformed waqf management, enhancing efficiency, transparency, and inclusiveness in community-based economic empowerment. This study aims to analyse digital innovation in waqf management in West Java and its contribution to strengthening the community economy within Indonesia’s legal framework, particularly the Electronic Information and Transactions Law (Law No. 11 of 2008). Employing a qualitative case study design, data were collected through interviews, observation, documentation, and literature review. The findings reveal that waqf institutions in West Java have adopted digital applications, crowdfunding platforms, QRIS payment systems, and online dashboards that increase wakif participation, transparency, and the growth of MSMEs and employment. However, challenges persist in digital literacy and infrastructure readiness. Digital waqf has strong potential as a sustainable economic empowerment instrument through professional governance, adaptive regulation, and reliable technological systems.